Pengaruh Pajak Tangguhan, Kompensasi Manajemen dan Sales Growth Terhadap Manajemen Pajak - Riana Rizky, Riana; Hasanah, Neneng (Jurnal Nusa Akuntansi, 2024)
This research aims to examine the influence of Deferred Tax, Management Compensation and Sales Growth on Tax Management. The independent variables used are Deferred Tax, Management Compensation and Sales Growth. The dependent variable used is Tax Management. This research is a type of quantitative research using secondary data. The population in this research is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange in 2018 - 2022. The method used is purposive sampling because this research has certain sample criteria which are adjusted to the research objectives. Based on the purposive sampling method, the number of samples in this study was 110 samples. In testing the hypothesis using panel data testing with the help of the Eviews version 12 program. Based on the results of the F test, it can be seen that the variables Deferred Tax, Management Compensation and Sales Growth together have an influence on Tax Management. Based on the results of the t test, it can be seen that the Deferred Tax variable has no effect on Tax Management. Management Compensation Variables influence Tax Management. The Sales Growth variable influences Tax Management.